Formic acid poisoning. Issue 661 (November 1980) - Jefferys, D. B.; Wiseman, H. M.
Abstract : Forty-five cases of formic acid poisoning are reviewed. The metabolic and pathological consequences of such overdoses are considered. The consequences are discussed in relation to the amount of the acid ingested. The problems likely to be encountered in the management of such patients are highlighted.